Ética e estética na (auto)ficção de Michel Laub e Imre Kertész - Bianchi, Bruno Jesus (2018)
The relations between history and literature have been strongly polemized from a broad spectrum of contemporary productions which attest to the figurations of historical elements within avowedly fictional narratives. Thus this research aims to promote the debate around some ethical implications enhanced in the works Diary of the fall (2011), by Michel Laub, and Liquidation (2003), by Imre Kertész, considering the articulation that is established in both narratives between fiction, the incorporation of autobiographical elements and memory of the Holocaust. Taking into account the gradual death of the last survivors of the Holocaust and the verification of the use of historical data in contemporary fiction, will be investigated the ways in which the writing of oneself, far from relativizing the barbarity in benefit of a narcissistic celebration of the author it can contribute to the maintenance of the memory of catastrophes allied, simultaneously to the gesture of remembrance of traumatic events in collective history from the point of view of the vanquished, advocated by Walter Benjamin in the Theses on the Philosophy of History (1940), and the Derridean task of rethinking politics, considering the understanding of the other as someone radically other than myself and the need to admit an utmost responsibility with the survival. The dialogues will be constructed from the theoretical subsidies of some thinkers such as Giorgio Agamben, Walter Benjamin, Jacques Derrida, Maurice Blanchot, among others.